Cariprazine (RGH-188), a potent D 3/D 2 dopamine receptor partial agonist, binds to dopamine D 3 receptors in vivo and shows antipsychotic-like and procognitive effects in rodents - Gyertyán, István; Kiss, Béla; Sághy, Katalin; Laszy, Judit; Szabó, Györgyi; Szabados, Tamás; Gémesi, Larisza I.; Pásztor, Gabriella; Zájer-Balázs, Mária; Kapás, Margit; Csongor, Éva Ágai; Domány, György; et al. (Neurochemistry international, 2011)
[Display omitted] ► Cariprazine, a D 3/D 2 partial agonist potently bound rat D 3 and D 2 receptors in vivo. ► Cariprazine had high potency and efficacy in preclinical antipsychotic screening tests. ► Cariprazine lacked cataleptogenic activity in rats. ► Cariprazine showed procognitive effects in scopolamine-impaired rats. We investigated the in vivo effects of orally administered cariprazine (RGH-188; trans- N-{4-[2-[4-(2,3-dichlorophenyl)-piperazin-1-yl]-ethyl]-cyclohexyl}- N′, N′-dimethyl-urea), a D 3/D 2 dopamine receptor partial agonist with ∼10-fold preference for the D 3 receptor. Oral bioavailability of cariprazine at a dose of 1 mg/kg in rats was 52% with peak plasma concentrations of 91 ng/mL. Cariprazine 10 mg/kg had good blood–brain barrier penetration, with a brain/plasma AUC ratio of 7.6:1. In rats, cariprazine showed dose-dependent in vivo displacement of [ 3H](+)-PHNO, a dopamine D 3 receptor-preferring radiotracer, in the D 3 receptor-rich region of cerebellar lobules 9 and 10. Its potent inhibition of apomorphine-induced climbing in mice (ED 50 = 0.27 mg/kg) was sustained for 8 h. Cariprazine blocked amphetamine-induced hyperactivity (ED 50 = 0.12 mg/kg) and conditioned avoidance response (CAR) (ED 50 = 0.84 mg/kg) in rats, and inhibited the locomotor-stimulating effects of the noncompetitive NMDA antagonists MK-801 (ED 50 = 0.049 mg/kg) and phencyclidine (ED 50 = 0.09 mg/kg) in mice and rats, respectively. It reduced novelty-induced motor activity of mice (ED 50 = 0.11 mg/kg) and rats (ED 50 = 0.18 mg/kg) with a maximal effect of 70% in both species. Cariprazine produced no catalepsy in rats at up to 100-fold dose of its CAR inhibitory ED 50 value. Cariprazine 0.02–0.08 mg/kg significantly improved the learning performance of scopolamine-treated rats in a water-labyrinth learning paradigm. Though risperidone, olanzapine, and aripiprazole showed antipsychotic-like activity in many of these assays, they were less active against phencyclidine and more cataleptogenic than cariprazine, and had no significant effect in the learning task. The distinct in vivo profile of cariprazine may be due to its higher affinity and in vivo binding to D 3 receptors versus currently marketed typical and atypical antipsychotics.